NIKAH KONTRAK MENURUT HUKUM ISLAM DAN REALITAS DI INDONESIA - Shafra Shafra (Marwah: Jurnal Perempuan, Agama dan Jender, 2010)
The aim of this article is to give the understanding of nikah mut’ah. It had been allowed in Islam in form of rukhsah. It is not halal or may absolutely. Then, it was prohibited forever and ever. Sunni prohibited it whereas Syi'ah allowed it. Rasullah’s friends did nikah mut’ah because they were far from house in order to battling and military operation. A period of that was also still represented transitory time of habit of Jahiliyah. For a while, in Indonesia most of nikah mut’ahs did because of sex, and finances. Marriage contract may not comprehend simply then it is legal on behalf of religion, because it is assumes more respectable compared to adultery.